Learning experience design of an mHealth intervention for parents of children with epilepsy. (April 2022) - Schmidt, Matthew; Glaser, Noah; Riedy, Tina; Rietta, Carmen; Huszti, Heather; Wagner, Janelle; Smith, Gigi; Gutierrez-Colina, Ana M.; Wetter, Sara E.; Guilfoyle, Shanna M.; Patel, Anup; Modi, Avani C.
Highlights: Anti-seizure medicinal adherence is a challenge for care providers. Few interventions exist to address adherence in pediatric epilepsy. Mobile technologies present promising new opportunities for intervention. Usability and user experience is a concern in technology-driven interventions. Learning experience design leads to effective, efficient, appealing interventions. Abstract: Purpose: The purpose of this paper is to describe the iterative design, development, and evaluation of a novel mHealth learning environment for parents of children with epilepsy. The mHealth learning environment is a component of a broader behavioral intervention called eACT (Epilepsy Adherence in Children and Technology), which seeks to improve antiepileptic drug adherence in children with epilepsy. The eACT mHealth learning environment integrates theoretical principles from the learning sciences with user-centered design methods and advanced learning technologies to provide an efficient and appealing learning experience that is specifically tailored to adult learners. Methods: The eACT mHealth learning environment was developed by a multidisciplinary team of experts across three major phases including: 1) preparation, 2) iterative design, and 3) iterative development. The preparation phase included developing user personas and conducting focus groups, which identified user needs and use cases for the product. The iterative learning experience design process made use of rapid prototypes in which the product design was improved between versions, resulting in a final design proof. Usability and user experience methods were deployed to evaluate the system during the iterative development phase. Results: Results from three phases of iterative design and development are presented through user personas, usability data, and qualitative analysis. Findings suggest the eACT mHealth learning environment is highly usable and relevant to the unique needs of adult caregivers of children with epilepsy. Findings also suggest that user experience was largely positive. Conclusions: This paper reveals key insights about how formative learning experience design processes can lead to highly relevant and usable interventions for adult learners.